Investigating the phytochemical composition of Curcuma longa , Azadirachta indica , and Asparagus racemosus using network pharmacology and molecular docking approaches for ovarian cancer therapy - Seneha Santoshi; Aastha Tanwar; Riddhi Bahri; Navya Aggrawal; Deepak Ganjewala; Hina Bansal (Zeitschrift für Naturforschung C, 2026)
Abstract Given that ovarian cancer is a major health concern for women worldwide, we explored the potential of Indian medicinal plants, namely Curcuma longa (Turmeric), Azadirachta indica (Neem), and Asparagus racemosus (Shatavari) via a combined approach of network pharmacology and molecular docking. Initially, bioactive phytochemicals of these plants were sourced from the IMPPAT and SwissTargetPrediction databases, resulting in the identification of 202 compounds along with 1,124 corresponding protein targets. These were then compared with ovarian cancer–related genes obtained from the GeneCards database, leading to the identification of 885 common targets. A protein–protein interaction network was constructed and analyzed using Cytoscape to identify the cluster modules. Additionally, gene ontology and pathway enrichment analyses revealed the multifaceted nature of ovarian cancer, indicating its disruptive impact on various cellular processes, signaling pathways, immune responses, and metabolic regulations. Importantly, EGFR, PIK3CA, JAK2, and PIK3CD were identified as crucial therapeutic nodes within the network. Subsequent molecular docking recognized the strong binding affinity between the active compounds and these key targets, thereby supporting the network analysis. In conclusion, the study highlighted the therapeutic action of C. longa , A. indica , and A. racemosus in combating ovarian cancer and promoting the development of plant-based treatments for this cancer.